Caucasian lean subjects with non-alcoholic fatty liver disease share long-term prognosis of non-lean: time for reappraisal of BMI-driven approach? - Ramy Younes; Olivier Govaere; Salvatore Petta; Luca Miele; Dina Tiniakos; Alastair D. Burt; Ezio David; Fabio Maria Vecchio; Marco Maggioni; Daniela Cabibi; Duncan McLeod; María Jesús Pareja; et al. (2021)
Objective The full phenotypic expression of non-alcoholic fatty liver disease (NAFLD) in lean subjects is incompletely characterised. We aimed to investigate prevalence, characteristics and long-term prognosis of Caucasian lean subjects with NAFLD. Design The study cohort comprises 1339 biopsy-proven NAFLD subjects from four countries (Italy, UK, Spain and Australia), stratified into lean and non-lean (body mass index (BMI) </≥25 kg/m 2 ). Liver/non-liver-related events and survival free of transplantation were recorded during the follow-up, compared by log-rank testing and reported by adjusted HR. Results Lean patients represented 14.4% of the cohort and were predominantly of Italian origin (89%). They had less severe histological disease (lean vs non-lean: non-alcoholic steatohepatitis 54.1% vs 71.2% p<0.001; advanced fibrosis 10.1% vs 25.2% p<0.001), lower prevalence of diabetes (9.2% vs 31.4%, p<0.001), but no significant differences in the prevalence of the PNPLA3 I148M variant (p=0.57). During a median follow-up of 94 months (>10 483 person-years), 4.7% of lean vs 7.7% of non-lean patients reported liver-related events (p=0.37). No difference in survival was observed compared with non-lean NAFLD (p=0.069). Conclusions Caucasian lean subjects with NAFLD may progress to advanced liver disease, develop metabolic comorbidities and experience cardiovascular disease (CVD) as well as liver-related mortality, independent of longitudinal progression to obesity and PNPLA3 genotype. These patients represent one end of a wide spectrum of phenotypic expression of NAFLD where the disease manifests at lower overall BMI thresholds. Lay summary NAFLD may affect and progress in both obese and lean individuals. Lean subjects are predominantly males, have a younger age at diagnosis and are more prevalent in some geographic areas. During the follow-up, lean subjects can develop hepatic and extrahepatic disease, including metabolic comorbidities, in the absence of weight gain. These patients represent one end of a wide spectrum of phenotypic expression of NAFLD.